Host Immune Response Triggered by Graphene Quantum-Dot-Mediated Photodynamic Therapy for Oral Squamous Cell Carcinoma - Zhang X; Li H; Yi C; Chen G; Li Y; Zhou Y; Chen G; Li Y; He Y; Yu D (International Journal of Nanomedicine, 2020)
Xiliu Zhang,1 Hongyu Li,1,* Chen Yi,1,* Guosheng Chen,2 Ye Li,1 Ying Zhou,1 Guanhui Chen,1 Yiming Li,1 Yi He,1 Dongsheng Yu1 1Guanghua School of Stomatology, Hospital of Stomatology, Sun Yat-Sen University, Guangdong Provincial Key Laboratory of Stomatology, Guangzhou 510055, People’s Republic of China; 2MOE Key Laboratory of Bioinorganic and Synthetic Chemistry, School of Chemistry, Sun Yat-Sen University, Guangzhou 510275, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dongsheng YuGuanghua School of Stomatology, Hospital of Stomatology, Sun Yat-Sen University, Guangdong Provincial Key Laboratory of Stomatology, Guangzhou 510055, People’s Republic of ChinaEmail yudsh@mail.sysu.edu.cnIntroduction: With the innovation of photosensitizers, photodynamic therapy is now widely used in antitumor detection and treatment. Graphene quantum dots (GQDs) are proposed as a promising alternative photosensitizer due to their high biocompatibility, specific photoactivity, and strong tumor concentration. However, the changes in host immunity triggered by GQDs have only rarely been reported.Methods: In this work, GQDs as photosensitizers were conjugated to polyethylene glycol (PEG) to enhance solubility and blood circulation. The phototoxicity of the resulting GQD-PEG nanomaterials was then detected in vitro and in vivo. The antitumor immunity triggered by GQD-PEG under irradiation was further evaluated in an oral squamous cell carcinoma animal model.Results: The obtained GQD-PEG nanomaterials exhibited low cytotoxicity, good solution stability, and excellent endocytosis. Both in vitro and in vivo, all demonstrated strong ablation for oral squamous cell carcinoma under irradiation. Meanwhile, host-immunity-related CD8+ T cells (cytotoxic T lymphocytes) and proinflammatory cytokines, including IFN-γ and TNF-α, were significantly increased after photo-activated antitumor activity.Conclusion: These results highlight the dominant role of GQD-PEG in photodynamic therapy and could have significant implications for further combination therapy as a promising antitumor immune response strategy triggered by nanomaterials.Keywords: graphene quantum dots, photodynamic therapy, host immunity, oral squamous cell carcinoma